Tanggung Jawab Ayah terhadap Pemenuhan Nafkah Anak Pasca Perceraian - M. Adnan Lira (CV. Social Politic Genius (SIGn), 2023)
This study aims to understand responsibility and identify factors influencing a father’s inability to provide child support post-divorce. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that the primary responsibility for child support and education costs post-divorce lies with the father. The father’s failure to fulfill this responsibility results in serious consequences, both legally and socially. Factors influencing a father’s inability or failure include deteriorating economic conditions post-divorce, limited communication between father and child, and situations where the mother is financially more stable and takes over the role of providing child support. Therefore, it is recommended that relevant stakeholders develop policies and programs that support fathers post-divorce in meeting their responsibilities for child support and children’s educational expenses. It is vital to provide fathers access to economic resources, training, and legal assistance to help them overcome financial difficulties post-divorce. Additionally, there should be facilitation of more effective communication between father and child, involving counseling or family mediation. In situations where the mother has better financial stability, stakeholders should consider a balance in the division of child support responsibilities, enabling both parents to contribute according to their capabilities. This approach will help minimize negative impacts on the child and acknowledge the changing socio-economic dynamics post-divorce.